Effects of Food on the Bioavailability of Amphetamine in Healthy Adults After Administration of SHP465 Mixed Amphetamine Salts Extended-Release Capsules - Yi Wang; Ming Yu; Brian Yan; Patrick Martin; Brigitte Robertson (Adis, Springer Healthcare, 2019)
Abstract Background and objective SHP465 mixed amphetamine salts extended release is a once-daily, single-entity, mixed amphetamine salts capsule product for attention-deficit/hyperactivity disorder. The objective of this study was to evaluate amphetamine pharmacokinetics following SHP465 mixed amphetamine salts under three administration conditions. Methods Healthy adults (n = 16) enrolled in an open-label, randomized, three-period crossover study with three single-dose 50-mg SHP465 mixed amphetamine salts treatments (fasting ≥ 10 h before administration [reference]; high-fat meal consumption 30 min before administration; sprinkling capsule contents on applesauce) separated by ≥ 7-day washouts. Blood samples for evaluating d- and l-amphetamine pharmacokinetics were collected pre-dose and up to 60 h post-dose. Assessments included maximum plasma concentration, time to maximum plasma concentration, and area under the plasma concentration-time curve from 0 to infinity. Exponentiated least-squares mean ratios with 90% confidence intervals for test treatments relative to the reference treatment were calculated, with the absence of an effect indicated by the 90% confidence intervals falling within the 80-125% range. Results Least-squares mean (90% confidence interval) ratios for maximum plasma concentration and area under the plasma concentration-time curve from 0 to infinity indicated neither consuming a high-fat meal (d-amphetamine: 85.33 [80.44, 90.50] and 91.11 [86.69, 95.75], respectively; l-amphetamine: 85.22 [80.18, 90.59] and 88.74 [83.89, 93.87]) nor sprinkling the capsule contents on applesauce (d-amphetamine: 95.76 [90.28, 101.57] and 95.77 [91.13, 100.65]; l-amphetamine: 96.90 [91.16, 103.00] and 94.78 [89.60, 100.26]) altered amphetamine exposure. Consuming a high-fat meal prolonged median time to maximum plasma concentration for d- and l-amphetamine by 5.0 and 4.5 h, respectively, relative to reference treatment. Conclusions These findings demonstrate SHP465 mixed amphetamine salts capsules can be swallowed whole with or without food or the capsule contents can be sprinkled on applesauce.